Approaches to the Narrative Itinerary of José Martí - Nuñez-Rodríguez, Mauricio (2019)
This essay approaches the side of José Martí as narrator, which has remained in the periphery of the critics’ interest due to the poetic, journalistic and revolutionary work of the author. It delves into a group of pieces that constitute a narrative system itself in his literary work not following the traditional canon